Informality as a stepping stone: A search-theoretical assessment of informal sector and government policy - Semih Tümen (Central Bank Review (CBR), 2016)
This paper develops a model of sequential job search to understand the factors determining the effect of tax and enforcement policies on the size (i.e., employment share) of informal sector. The focus is on the role of informal sector as a stepping stone to formal jobs. I argue that the stepping-stone role of informal jobs is an important concept determining how strongly government policies affect the size of informal sector. I measure the extent of the stepping-stone role with the intensity of skill accumulation in the informal sector. If informal jobs help workers acquire skills, gain expertise, and build professional networks for boosting the chances to switch to a formal job, then the size of informal sector is less sensitive to government policy. In this case, the option value of a job in informal sector will be high and a worker with an informal job will not rush to switch to a formal job when a policy encouraging formal employment is in effect. If, on the other hand, informal sector does not provide satisfactory training opportunities, then the size of informal sector becomes more sensitive to government policy. Calibrating the model to the Brazilian data, I perform numerical exercises confirming that the effect of government policy on the size of informal sector is a decreasing function of the intensity of skill acquisition in the informal sector.
Keywords: E26; J24; J38; J64; 330; Informal sector; Stepping stone; Government policy; Job search; Human capital; Option value